2004
DOI: 10.1097/00008571-200411000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of common polymorphisms in reduced folate carrier and ??-glutamylhydrolase to methotrexate polyglutamate levels in patients with rheumatoid arthritis

Abstract: We investigated whether polymorphisms in reduced folate carrier (SLC19A1 G80A) and gamma-glutamyl-hydrolase (GGH-401C/T) are predictive of methotrexate polyglutamate (MTXPG) levels in patients with rheumatoid arthritis treated with weekly low-dose methotrexate (MTX). Adult patients treated with MTX were enrolled in a multicentred study. Blood was drawn at the time of the visit, DNA was extracted and red blood cell (RBC) MTXPG levels (up to the penta-order of glutamation) were measured by high-performance liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
101
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(111 citation statements)
references
References 36 publications
5
101
0
5
Order By: Relevance
“…An increased toxicity observed in this group of patients may be related to elevated levels of MTX polyglutamates seen in RFC-1 80AA individuals. 18 These observations are in keeping with previous studies, which demonstrated an association between increased MTX polyglutamate levels and hepatotoxic effects of the drug. 19,20 In a previous study Laverdiere et al 8 suggested an influence of RFC-1 gene (G80A) polymorphism on MTX plasma levels and treatment outcome of childhood acute lymphoblastic leukemia.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…An increased toxicity observed in this group of patients may be related to elevated levels of MTX polyglutamates seen in RFC-1 80AA individuals. 18 These observations are in keeping with previous studies, which demonstrated an association between increased MTX polyglutamate levels and hepatotoxic effects of the drug. 19,20 In a previous study Laverdiere et al 8 suggested an influence of RFC-1 gene (G80A) polymorphism on MTX plasma levels and treatment outcome of childhood acute lymphoblastic leukemia.…”
Section: Discussionsupporting
confidence: 91%
“…However, the polymorphism could also directly impact disease activity through more subtle alteration in folate homeostasis. 15,18 In our study hepatotoxicity, measured as ALT and AST activities, after MTX treatment was observed in some 4-5% of patients and more frequently affected individuals with RFC-1 80AA (10.5%) genotype than 80GG genotype (2.3%). An increased toxicity observed in this group of patients may be related to elevated levels of MTX polyglutamates seen in RFC-1 80AA individuals.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…To date, most studies have shown that the MTHFR C677T genotype is related to biomarkers, such as serum folate, tHcy concentration, and folate intake. Other polymorphisms in the folate pathway have been found to be associated with a variety of complex traits and disorders including MTHFR A1298C, MTRR A66G, MTR A2756G, MTHFD1 G1958A, FOLH1 T484C, SLC19A1 A80G, and transcobalamin II ( TCN2 ) C776G, the transport protein of vitamin B12 (Weisberg et al 1998; Gaughan et al 2001; Laverdiere et al 2002; Kluijtmans et al 2003; Dervieux et al 2004; Martinelli et al 2006; Moskau et al 2007; Silva et al 2011; Pangilinan et al 2012; Xie et al 2012). Table 1 summarizes the distribution of serum tHcy, folate, vitamin B6, and vitamin B12 according to polymorphisms related to folate and tHcy metabolism (Hiraoka et al 2004; Hiraoka et al 2009).…”
Section: Genetic Polymorphisms Related To Folate and Thcy Metabolism mentioning
confidence: 99%
“…65 Gamma-glutamyl hydrolase (GGH; EC, 3.4.19.9) catalyzes the hydrolysis of folylpoly-gamma-glutamates by removing g-linked glutamate and polyglutamates. Similar to a number of other genes within the one-carbon folate pathway, polymorphisms in the GGH gene have been associated with lower response to administration of the anti-folate, methotrexate, for the treatment of various conditions including rheumatoid arthritis 66 and acute lymphoblastic leukemia. 67 The enzyme 5-aminoimidazole-4-carboxamide ribonucleotide formyltransferase/IMP cyclohydrolase (ATIC; EC, 2.1.2.3) is able to convert 10-formyl THF to THF (Figure 1).…”
Section: Homocystinuria and Hypomethionemiamentioning
confidence: 99%